Precision Oncology via Radiotherapy‐Triggered Drug Delivery: Mechanisms, Molecular Engineering, and Clinical Translation - Jianv Jiang; Tanfeng Zhang; Junliang Dong; Wenjing Sun (Advanced Science, 2026)
ABSTRACT Radiotherapy‐triggered drug delivery systems (RDDS) promise to integrate the spatial precision of ionizing radiation with controllable pharmacological activation. However, clinical translation remains constrained by its reliance on supra‐clinical irradiation doses. Here, we present a unifying framework redefining RDDS through two distinct paradigms: structural disassembly and molecular actuation. We delineate their radiochemical foundations, highlighting reductive and electron‐driven mechanisms as more robust and tumor‐selective than stochastic reactive oxygen species‐mediated pathways. Furthermore, we position radiation‐driven gas therapy as a distinct modality based on in situ molecular generation. Critically, we identify the dose–response mismatch between radiolytic chemistry and clinical radiation as the central translational bottleneck. To overcome this, we propose a design paradigm centered on highly predictable, dose‐matched activation, where mechanisms directly coupling radiation energy to molecular transformation offer superior predictability. Finally, we explore the integration of RDDS with imaging and artificial intelligence to create closed‐loop, feedback‐controlled systems. This review establishes a conceptual and translational roadmap, envisioning the evolution of radiotherapy from a purely cytotoxic modality into a programmable actuator for precision oncology.